Ignorance, Intention and Stochastic Outcomes - Jana Friedrichsen; Katharina Momsen; Stefano Piasenti (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2020)
Intentions play a fundamental role in many situations characterized by nonsimultaneous interaction from principal-agent settings in firms to the international task of protecting the environment and the climate. We experimentally investigate how decision makers (DMs) respond to perceived intentions of a matched partner and a stochastic, imperfectly informative outcome when choosing a reciprocating action. We vary if the DM observes their partner's action or only the outcome before taking their own decision. Observing no evidence of an outcome bias, we find that the DM reciprocates good intentions under full information. However, reciprocity of DMs is lower in the treatment where information on the partner's action is hidden. Our analysis suggests that this is driven by the partners? behavior. DMs select into being informed or uninformed based on their inclination to behave more or less prosocially. While information avoidance is frequent, we do not find evidence for moral wiggling. In line with the absence of moral wiggling, an analysis of subjects' beliefs speaks against strategic cynicism.
Keywords: D91; C91; 330; information avoidance; dictator game; public good game; moral wiggleroom; intentions; reciprocity